Analysis of Misuse of Eyd in Elementary School Students of SD Negeri Sangiang Jaya - Oktavia, Putri; Sa’odah, Sa’odah; Ginanjar, Romi Ramdon (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Education is a process, namely the process of maturing students. This process is carried out by educators consciously and responsibly. Children who have difficulty in one or more of these difficulties usually have low achievement and grades in certain subjects. Research Focus, determining what factors cause students to have difficulty writing EYD, especially the use of capital letters, periods and commas, students' problems in using EYD (capital letters, periods, commas), problem formulation based on the background of the problem So the formulation of the problem in the research is, what difficulties do students have in using EYD, how many mistakes do students make in writing narrative essays in accordance with EYD, research objectives In accordance with the problem formulation that has been determined, the objectives to be achieved in this research namely, describing what factors cause students to have difficulty writing EYD, describing what mistakes students make in using EYD.